2022
DOI: 10.1111/myc.13558
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the clinical features and risk factors for children tinea capitis complicated with allergic diseases

Abstract: Background Tinea capitis, atopic dermatitis and allergic rhinitis are the most common disorders endured by prepubescent children. Dermatophyte infections have been linked to allergic disorders, such as increased sensitivity to dermatophytes in patients with atopic dermatitis. Objectives To explore the correlation between tinea capitis and allergic diseases in children and to analyse their risk factors. Methods This study monitored epidemiological changes in childhood tinea capitis and risk factors for whom wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…34 In our study, 6.6% of patients with kerion had had AD before, which was significantly higher than the rate of patients with noninflammatory TC (0.8%), as skin barrier dysfunction and reduced production of epidermal antimicrobial peptides in AD patients could trigger severe skin infections. 35,36 Our study also indicated that animal contact could increase the risk of kerion development, as animals could be healthy carriers of geophilic and zoophilic pathogens [37][38][39] due to their 'burrowing and denning' habits and contact with other animals. Interestingly, endothrix hyphae were also related to kerion occurrence.…”
Section: Discussionmentioning
confidence: 64%
“…34 In our study, 6.6% of patients with kerion had had AD before, which was significantly higher than the rate of patients with noninflammatory TC (0.8%), as skin barrier dysfunction and reduced production of epidermal antimicrobial peptides in AD patients could trigger severe skin infections. 35,36 Our study also indicated that animal contact could increase the risk of kerion development, as animals could be healthy carriers of geophilic and zoophilic pathogens [37][38][39] due to their 'burrowing and denning' habits and contact with other animals. Interestingly, endothrix hyphae were also related to kerion occurrence.…”
Section: Discussionmentioning
confidence: 64%
“…The percentage of a history of animal contact was over 65.21% (15/23) in our study and thus pet holding is an obvious risk factor for zoophilic pathogen infection. 36 In Italy, 46 cases of tinea faciei due to M. canis were reviewed, 39.13% (18/46) of the cases involving the vellus hair follicle.…”
Section: Discussionmentioning
confidence: 99%